2020
DOI: 10.1177/0748233720954995
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of heavy metals, lipid profiles, and antioxidant status of snails (Achatina achatina)around cement factory vicinities

Abstract: Some snails ( Achatina spp) can be used as a biosensor of heavy metal poisoning. This study thus estimated some heavy metal levels, antioxidant markers, and lipid profiles of snails handpicked around cement factory vicinities in Ogun State, Nigeria. Snails and soil samples were collected from Oke, Ewekoro, Papalanto, and Mowodani Imeko-Afon (control site). Lead (Pb), cadmium (Cd), and arsenic (As) levels were estimated in the soil, snail foot, hemolymph, and shell using Atomic Absorption Spectrophotometry. Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
(42 reference statements)
2
10
0
Order By: Relevance
“…In the case of this study, the heavy metal-loaded dust removed from the lungs may have found its way to the GIT where they stimulate similar pathophysiological mechanisms. Similar evidence was recently reported by [ 31 ] who found significantly high levels of heavy metal in visceral organs of rats co-exposed to cadmium and lead, and [ 32 ] who similarly found significantly high levels of heavy metals in various tissues of snails picked around cement factory. Also, in plant physiology, similar evidence has been reported where heavy metallic constituents of cement dust have been demonstrated to leach into the soil around cement factory site causing a significantly higher proportion of toxic metal within the factory neighborhood [ 2 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the case of this study, the heavy metal-loaded dust removed from the lungs may have found its way to the GIT where they stimulate similar pathophysiological mechanisms. Similar evidence was recently reported by [ 31 ] who found significantly high levels of heavy metal in visceral organs of rats co-exposed to cadmium and lead, and [ 32 ] who similarly found significantly high levels of heavy metals in various tissues of snails picked around cement factory. Also, in plant physiology, similar evidence has been reported where heavy metallic constituents of cement dust have been demonstrated to leach into the soil around cement factory site causing a significantly higher proportion of toxic metal within the factory neighborhood [ 2 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…3). The increment is consistent in studies involving heavy metals intoxication [56,57,5], and might be due to arsenic-induced increased free radicals production [5]. Indeed, lipid peroxidation due to electron abstraction by free radicals is common during heavy metals toxicity [5,58,59].…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, reductions in liver, kidney, and plasma thiol levels, as observed in this study, might be due to the irreversible binding of the metabolized arsenicals to the SH-group of the liver and kidney proteins [43]. Because these xenobioticdetoxifying enzyme depends on and requires the electron-donating potential of reduced glutathione (a thiol-containing tripeptide), and other thiol-rich compounds for their effects, their activity is impaired by lack of substrate [5]. Regardless, flavonoid fractions of C. volubile and V. amygdalina (FCV and FVA) either singly or, in combination, reversed the decrements of total thiol levels in the plasma, liver and kidneys.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations